Subjective Knowledge in Consumer Financial Decisions - Hadar, Liat; Sood, Sanjay; Fox, Craig R. (Journal of Marketing Research, 2013)
The authors propose that attempts to increase consumers’ objective knowledge (OK) regarding financial instruments can deter willingness to invest when such attempts diminish consumers’ subjective knowledge (SK). In four studies, the authors use different SK manipulations and investment products to show that investment decisions are influenced by SK, independent of OK. Specifically, they find that (1) willingness to pursue a risky investment increases when SK is high (vs. low) relative to a prior investment choice (Study 1); (2) willingness to enroll in a retirement saving program is enhanced by asking consumers an easy (vs. difficult) question about finance, thereby increasing SK (Study 2); (3) technically elaborating information about a mutual fund diminishes SK regarding that investment and decreases choice of that fund (Study 3); and (4) consumers invest less money in funds when missing information is made salient, holding the objective investment information constant (Study 4). Furthermore, the effects in Studies 2–4 are mediated by participants’ self-rated SK. The authors propose that effective financial education must focus not only on imparting relevant information and enhancing OK but also on promoting higher levels of SK.